Berio's Sequenzas: Essays on performance, composition and analysis - Halfyard, Janet K. (Surrey Ashgate, 2007)
Between 1958 and 2002, Luciano Berio wrote fourteen pieces entitled "Sequenza", along with several versions of the same work for different instruments, revisions of the original pieces and also the parallel "Chemins" series, where one of the "Sequenzas" is used as the basis for a new composition on a larger scale. The "Sequenza" series is one of the most remarkable achievements of the late twentieth century. It is a collection of virtuoso pieces that explores the capabilities of a solo instrument and its player, making extreme technical demands of the performer whilst developing the musical vocabulary of the instrument in compositions so assured and so distinctive that each piece both initiates and potentially exhausts the repertoire of a new genre.The "Sequenzas" have significantly influenced the development of composition for solo instruments and voice, and there is no comparable series of works in the output of any other composer. Series of pieces tend to be linked by the instruments for which the composer writes, but this is a series in which the pieces are linked instead by the variety of instruments for which Berio composed. The varied approaches taken by the contributors in discussing the pieces demonstrate the richness of this repertoire and the many levels on which Berio and these landmark compositions can be considered. Contributions are arranged under three main headings: Performance Issues; Berio's Compositional Process and Aesthetics; Analytical Approaches.